An integrated study of Dark Earth from the alluvial valley of the Senne river (Brussels, Belgium). (1st December 2017) - Devos, Yannick; Nicosia, Cristiano; Vrydaghs, Luc; Speleers, Lien; van der Valk, Jan; Marinova, Elena; Claes, Britt; Albert, Rosa Maria; Esteban, Irene; Ball, Terry B.; Court-Picon, Mona; Degraeve, Ann
Abstract: The present article discusses the integration of urban geoarchaeological and archaeobotanical data of a series of Dark Earth deposits situated in the alluvial valley of the Senne River in Brussels, Belgium. Due to their homogeneous character, their interpretation is a huge challenge for archaeologists. Through a case-by-case approach, a detailed picture of the sequence of different activities and (semi-) natural events, leading to the build up of Dark Earth at each individual site has been obtained. Among the activities, agricultural practices and waste management, which are rarely archaeologically recorded in urban contexts, have been identified. Despite being situated in a valley context, none of the sites presented an excellent preservation of the organic plant remains. However, through the integration of geoarchaeological and botanical data, the taphonomical history of the botanical remains could better be understood, allowing us to document the evolution of the environment surrounding the sites. Additionally, it has been demonstrated that the botanical study of Dark Earth units can also provide valuable information on vegetal consumption, in particular fruits. On a broader scale, this integrated geoarchaeologial and archaeobotanical study sheds some light on the process of urbanisation of the Senne alluvial valley between the 11th–12th and the 16th century AD.